The dendritic cell receptor Clec9A: receptor regulation and immune modulation. (October 2022) - Tullett, Kirsteen M.; Tan, Peck Szee; Park, Hae-Young; Schittenhelm, Ralf B.; Michael, Nicole; Blewitt, Marnie; Caminschi, Irina; Shortman, Ken; Purcell, Anthony W.; Nicola, Nicos; Zhang, Jian-Guo; Lahoud, Mireille H.
Abstract : Dendritic cells (DC) use a variety of cell surface receptors to monitor the environment for potential dangers, including cells that have died of non-homeostatic causes (eg. infected cells), to induce appropriate immune responses. Clec9A is a DC-specific Damage-Associated Molecular Pattern receptor, that is expressed by mouse and human cross-presenting DC subsets. Clec9A recognises actin filaments exposed on dead cells, and facilitates the processing of dead cell-derived antigen (Ag) for the induction of effective immune responses. A major focus of our research is identification of the molecular mechanisms that underpin Clec9A function and the control of immune responses to dead cell-associated Ag, and on the development of Clec9A-targeting approaches for enhancing immune responses. We recently identified a novel intracellular Clec9A-binding partner, the E3 ubiquitin ligase, RNF41. We discovered RNF41 ubiquitinates Clec9A to regulate its downstream fate. Intriguingly, RNF41 ubiquitinates the extracellular domains of Clec9A, revealing a novel mechanism of receptor regulation. Furthermore, RNF41 regulates DC cross-presentation of Ag acquired from dead cells. Our research is now focussed on elucidating this novel pathway of Clec9A regulation, and the role of this pathway in regulating MHCI processing and presentation of dead cell Ag.